Programação Genética Aplicada no Processo de Descoberta de Conhecimento em Bases de Dados de Redes de Pesquisa. - DUARTE, Kedma Batista (2010)
The Genetic Programming (GP) is a heuristic algorithm for Data Mining (DM), which can be applied to the classification task. This is a method of evolutionary computing inspired in the mechanisms of natural selection theory of Charles Darwin, declared in 1859 in his book "The Origin of Species." From an initial population, the method search over a number of generations to find solutions adapted to the environment of problem. The PG method was proposed in 1990 by John Koza, who demonstrated in one of its applications, the induction in formation of decision trees in the process of data classification. Within this context, the study developed in this work has as main objective the investigation of the concepts of PG and its application on a database of scientific collaboration networks, helping as a management tool in prospective studies of trends for the establishment of common axes in public policy of Science, Technology and Innovation (STI), focusing on regional development. The method is applied on a set of attributes, sorting them in order to identify similarity relationships between groups of researchers that comprise the network. The study involves the concepts of Knowledge Discovery in Databases (KDD) and Data Mining (DM). Networks of Scientific Collaboration, or Networks Research, are inserted in the context of small groups of social networks, the environment is dynamic due to the easy of information exchange and links between individuals, favoring the formation of new groups, which makes the growth of the network unlimited. "The combination of these groups, generated by the relationships between them, appears as a case of multi-criteria decision, granting the application of some complexity. In this sense, it is intended to apply the method of PG for generation of classification rules that lead to the discovery of groups of researchers with similar traits, which in a planned process could be induced to form groups strengthened and consolidated. The study helps to exploit the potential of genetic programming as a classifier algorithm, as well as use it as a method to build tools to support planning and decision making in STI.